FILOSOFI PENDIDIKAN YANG INTEGRAL DAN HUMANIS DALAM PERSPEKTIF MANGUNWIJAYA - Agustinus Wisnu Dewantara (Bahasa Indonesia, 2018)
Mangunwijaya introduced humanist educational philosophy and integrality. Education, according to Mangunwijaya, must create a climate that allows the child to divide themselves into an independent person. Education should aim to deliver learners in recognizing and developing human potential itself into a whole (not just the brain, but all aspects of humanity: skilled, intelligent, piety, solidarity, capable, and responsible). An education system should be humane. That is, a system of compulsory education to respect human dignity, particularly in the person of the child. Schools should thus be understood as a division of talent and togetherness with others. Consequently, the teaching system should not be alienated from the life of the concrete. That is, not merely biased cognitive, intellectualist or mere romantic extreme, but really develop talent, art, language, manners, morals, taste, religiosity, and social life.